Associations of health related behaviour, social relationships, and health status with persistent physical activity and inactivity: a study of Finnish adolescent twins. Issue 5 (1st October 2002) - Aarnio, M; Winter, T; Kujala, U; Kaprio, J
Abstract : Objective: To examine the association between leisure time physical activity over a three year period and health related behaviour, social relationships, and health status in late adolescence as part of a nationwide longitudinal study. Methods: Five birth cohorts of adolescent twins aged 16 at baseline (n = 5028; 2311 boys and 2717 girls) participated in the study. Questionnaires on leisure time physical activity, other health related behaviour, social relationships, and health status were sent to the twins on their 16th and 17th birthdays and six months after their 18th birthday. The combined response rate to the three questionnaires was 75.8% for boys and 81.7% for girls. Those who answered in all three questionnaires that their frequency of physical activity was 4–5 times a week or more were defined as persistent exercisers, and those who exercised at most twice a month in all three were defined as persistently inactive. Logistic regression analyses were used to identify baseline variables associated with outcome measures. Results: Overall, 20.4% of boys and 13.0% of girls were persistent exercisers and 6.5% of boys and 5.3% of girls were persistently inactive. In both sexes, smoking, irregular breakfast eating, attending vocational school, and poor self perceived current health were significantly associated with persistent inactivity. Conclusions: Persistent physical inactivity in adolescents is associated with a less healthy lifestyle, worse educational progression, and poor self perceived health. Tailoring methods to promote physical activity may prove useful for influencing other health habits. Such programmes are indicated for vocational schools in particular.